Comparison of seismic and hydrodynamic yield determinations for the Soviet joint verification experiment of 1988 - Sykes, Lynn R. (1989)
Seismic magnitudes determined from surface and body waves for the Soviet underground nuclear explosion of September 14, 1988, are used to calculate the yield of that event from previously derived calibration curves. The yield obtained by combining the two seismic estimates is 113 kilotons, which is very close to those obtained by hydrodynamic measurements made on-site. This comparison substantiates previous conclusions about the sizes of past Soviet weapons tests and compliance with the Threshold Test Ban Treaty. The factor of uncertainty in the combined seismic yield is 1.28 at the 68% and 1.62 at the 95% confidence levels, demonstrating that accuracies considerably better than a factor of 2 can be obtained by combining seismic determinations of yield.